Pemilihan Karakter Agronomi untuk Menyusun Indeks Seleksi pada 11 Populasi Kedelai Generasi F6 - Wirnas, Desta; Widodo, Imam; Sobir, Sobir; Trikoesoemaningtyas, Trikoesoemaningtyas; Sopandie, Didy (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2006)
High-yielding variety is one of the targets in soybean breeding program. High-yielding variety could be developed through simultaneous selection. Simultaneous selection  using selection index was more efficient  than selection based on an individual trait only.  Objective of  the research was to select agronomic characters for construction selection index  on 11 soybean populations F6 generation based on correlation analysis, path analysis, and heritability.  The correlation analysis  showed that  number of branch,  number of total nod, number of filled pod, number of unfilled pod, number of total pod, and percentage of filled pod have positively and significantly correlated with  yield per plant.  Based on  path analysis, characters number of branch, number of unfilled pod, and number of filled pod have positive direct on yield per plant.   The result also showed that  number  of filled pod has maximum positive direct effect on yield per plant.  Generally, number of total nod, number of filled pod, number of total pod, and percentage of filled pod have higher heritability  than other characters.   Key words: Soybean, correlation, path analysis, heritability, selection index